Improving Students’ Learning Motivation Through Qailulah at Darussalam Kasomalang Islamic Boarding School, Subang, West Java - Nuriana, Didin (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
Learning enthusiasm is a crucial factor that determines students’ academic success in Islamic boarding schools (pesantren). However, the intensive 24-hour learning schedule often reduces concentration and leads to fatigue, which can weaken students’ motivation. This study aims to examine the effectiveness of Qailulah—a short midday nap rooted in the Sunnah of the Prophet Muhammad—in maintaining and improving students’ learning spirit. Using a descriptive qualitative approach, data were collected through observations, interviews with teachers and caregivers, and documentation analysis. The findings reveal that students who practice Qailulah demonstrate higher concentration, stronger memory, and better emotional stability compared to those who do not. Teachers also reported that afternoon and evening learning sessions became more effective after the implementation of Qailulah. This research concludes that institutionalizing Qailulah is not only a religious practice but also a strategic educational intervention to balance academic demands, physical health, and emotional resilience.